Monitoring the therapeutic efficacy of CA4P in the rabbit VX2 liver tumor using dynamic contrast-enhanced MRI - Tianzhuang Han; Qingqing Duan; Rong Yang; Yuzhe Wang; Huabin Yin; Fanhua Meng; Yongjuan Liu; Ting Qian (Diagnostic and Interventional Radiology, 2021)

(untitled)
PURPOSE:The present work aims to evaluate whether dynamic contrast-enhanced magnetic resonance Imaging (DCE-MRI) can monitor non-invasively the blocking effect on microvessels of the Combretastatin-A4-phosphate (CA4P) and assess the therapeutic efficacy. METHODS:Forty rabbits were implanted the VX2 tumors specimens. Two weeks later, serial MRI (T1 weighted image, T2 weighted image and DCE) were performed at 0 h, 4 h, 24 h, 3 d and 7 d after CA4P (10 mg/kg) or saline treatment. The parameters of DCE (Ktrans, Kep, Ve and iAUC60) of enhancement tumor portions were measured. Then all the tumor samples were stained to count microvessel density (MVD). At last, two-way repeated measures ANOVA was used to analyze the difference between and within groups. The correlation between the Ktrans, Kep, Ve, iAUC60 and MVD was analyzed by using the Pearson correlation analysis and Spearman's rank correlation.RESULTS:The Ktrans and iAUC60 in the CA4P group were lower than the values of the control group at 4 h after treatment, which have significant differences (D-value: -0.133 min-1, 95%CI: -0.169~-0.097 min-1，F = 59.109, p < 0.001 for Ktrans; D-value: -10.533 mmol/sec, 95%CI: -17.147~-3.919 mmol/sec，F = 11.110, and p = 0.003 for iAUC60). In the CA4P group, the Ktrans and iAUC60 reached the minimum values at 4 h. There were significant differences between 4 h and other different time points of the Ktrans and iAUC60 in the treatment group (all p < 0.01). The parameters Ktrans (r = 0.532, P = 0.016 and r = 0.681, P = 0.001, respectively) and iAUC60 (r = 0.580, P = 0.007 and r = 0.568, P = 0.009, respectively) of 7 days showed correlation with MVD in both groups, while Kep and Ve did not show correlation with MVD (P > 0.05). CONCLUSION:The blocking effect of microvessels after CA4P treatment can be evaluated by DCE-MRI, and the parameters of quantitative Ktrans and semi- quantitative iAUC60 can assess the change of the tumor angiogenesis noninvasively.